Operational stability of organic field-effect transistors - Bobbert, Peter A.; Sharma, Abhinav; Mathijssen, Simon G. J.; Kemerink, Martijn; Leeuw, Dago M. de (Advanced materials, 2012)
Organic field-effect transistors (OFETs) are considered in technological applications for which low cost or mechanical flexibility are crucial factors. The environmental stability of the organic semiconductors used in OFETs has improved to a level that is now sufficient for commercialization. However, serious problems remain with the stability of OFETs under operation. The causes for this have remained elusive for many years. Surface potentiometry together with theoretical modeling provide new insights into the mechanisms limiting the operational stability. These indicate that redox reactions involving water are involved in an exchange of mobile charges in the semiconductor with protons in the gate dielectric. This mechanism elucidates the established key role of water and leads in a natural way to a universal “stress function”, describing the stretched exponential-like time dependence ubiquitously observed. Further study is needed to determine the generality of the mechanism and the role of other mechanisms.
Gesehen am 12.12.2019